Fundamentals of database systems - Elmasri, Ramez (Pearson, 2016)
"This book introduces the fundamental concepts necessary for designing, using, and implementing database systems and database applications. Our presentation stresses the fundamentals of database modeling and design, the languages and models provided by the database management systems, and database system implementation techniques"--Page vii.